The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jcm10091808
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computer-Assisted Dynamic Navigation in Implant Placement with a Fully Digital Approach: A Prospective Clinical Trial

Abstract: Background: This prospective clinical study aimed to investigate a possible deviation between the digitally planned implant position and the position achieved using dynamic navigation. The aim of the study was to establish clinical effectiveness and precision of implantation using dynamic navigation. Methods: Twenty consecutive patients received an implant (iSy-Implantat, Camlog, Wimsheim, Germany). One screw implant was placed in one jaw with remaining dentition of at least six teeth. The workflow was fully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 49 publications
2
24
1
3
Order By: Relevance
“…In the present case, the deviations at the implant shoulder of teeth 36 and 37 were 0.831 mm and 0.682 mm, respectively; 0.574 mm and 0.867 mm at the implant apical level, respectively; and angular deviations of 3.118° and 2.317°, respectively. The results were consistent with preliminary studies on the accuracy of dynamic navigation surgeries[ 8 , 15 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present case, the deviations at the implant shoulder of teeth 36 and 37 were 0.831 mm and 0.682 mm, respectively; 0.574 mm and 0.867 mm at the implant apical level, respectively; and angular deviations of 3.118° and 2.317°, respectively. The results were consistent with preliminary studies on the accuracy of dynamic navigation surgeries[ 8 , 15 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Computer-assisted dynamic navigation systems (CADNSs) based on cone-beam computed topography (CBCT) navigation have been introduced into the field of dental implantology to improve the accuracy of implant placement and avoid potential complications[ 8 , 9 ]. A CADNS is a surgical navigation system which can design the location of a virtual implant according to CBCT data.…”
Section: Introductionmentioning
confidence: 99%
“…67 mm at entry point, 0.9 mm at apex and 2.50° of angular deviation) (Stefanelli et al, 2020 ). Edelmann and colleagues experienced mean deviations of 1.83 mm at entry point, 1.95 mm at apex, and 2.7° of angular deviation with another navigation system (Edelmann et al, 2021 ). A recently published systematic review and meta‐analysis on accuracy of surgery reported an average global platform deviation, global apex deviation, and angular deviation of 1.02 mm (95% CI 0.83–1.21), 1.33 mm (95% CI 0.98–1.67), and 3.59° (95% CI 2.09–5.09) and concluded it was clinically acceptable with potential in clinical usage (Wei et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning, this technology was adopted from implant dentistry. 13 In the field of endodontics, this technology was demonstrated to be safe, fast and accurate in preparing the access cavity, 14 15 locating calcified canals, [16][17][18] intraosseous anaesthesia, 19 removal of fibre posts from root canals 7 and endodontic microsurgery. 20 21 It has several advantages: (1) reducing time and cost; (2) conducive to cooling and avoiding damage to tissue due to heat production; (3) performing operations with insufficient space; (4) increased safety, accurate and predictability and (5) real-time visualisation of the position and angulation of the drill.…”
Section: Open Accessmentioning
confidence: 99%